The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.15244/pjoes/84918
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Antioxidant and Antibacterial Activity of Tunisian Date Palm Seed

Abstract: Date palm (Phoenix dactylifera L.) is an important crop in arid and semiarid regions. Date palm fruits constitute the principal source of remuneration and the basis of the economy for people living in the Tunisian Sahara. Phoenix dactylifera is a member of the family Arecaceae, also known as Palmaceae. It is well known that the average weight of date seeds is about 10-15% of date weight [1]. The fruit of the date palm is composed of a fleshy pericarp and seed. The edible part of date fruit is fleshy mesocarp, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(87 citation statements)
references
References 14 publications
3
53
3
1
Order By: Relevance
“…1% glucose, 4.56 ± 0.01% crude protein, 0.14 ± 0.04% crude fat and 3.82 ± 0.02% ash.These results are similar to values reported by other researchers on date varieties[24][25][26]. Total sugars/moisture content ratio (2.38) indicated that mature Deglet Nour dates are semi-dry fruit.…”
supporting
confidence: 91%
“…1% glucose, 4.56 ± 0.01% crude protein, 0.14 ± 0.04% crude fat and 3.82 ± 0.02% ash.These results are similar to values reported by other researchers on date varieties[24][25][26]. Total sugars/moisture content ratio (2.38) indicated that mature Deglet Nour dates are semi-dry fruit.…”
supporting
confidence: 91%
“…The high selectivity of acetone and ethanol can clarify the high content of phenolic compounds. The optimization of phenolic extraction from date seeds was investigated by Metoui et al (2019) and Al-Farsi et al (2007). They described TPCs of 9.53 and 10.3 mg GAE/g from varieties grown in Tunisia and Oman, respectively.…”
Section: Total Phenolic Contentmentioning
confidence: 99%
“…Date flesh extracts of the two cultivars exhibited antimicrobial activity that may be attributed to its bioactive components, for example, phenolic and flavonoid compounds due to the phenolic compound. Polyphenols assume an important role as an antibacterial activity through the protein precipitation and microorganism enzyme inhibition (El-Beltagi, Mohamed, Abdelazeem, Youssef, & Safwat, 2019c;Metou, Essid, Bouzoumita, & Ferchichi, 2019). Moreover, Maraei & Hamoud (2019) observed an increase in antioxidant and antimicrobial activity was parallel to an increase in phenolic compounds and flavonoid content due to irradiation treatment.…”
Section: Antimicrobial Activitymentioning
confidence: 99%